Vegetable producer and wholesaler attitudes toward implementing post-harvest practices in selected states of Peninsular Malaysia - Ruslan, Nur Aziera (2014)
Malaysia will continuously face impending international challenges and will affect its economic prospects considerably. With an increasing trend towards globalization,Malaysia will face sweeping technological changes in the production and processing of fresh produce, including fresh fruits and vegetables. Furthermore, in tandem with consumers’ awareness regarding to health conscience, they demand for better quality and safe fresh produce that is convenient and ready to be consumed. The objective of this study is to gather information about the attitudes toward implementing postharvest practices among fresh leafy vegetable producer and wholesaler. This study also covers the reasons for implementing/not implementing the practice of postharvest, namely the practice of washing, sorting and grading, storage, packaging, andlabeling. This study used the data collected from a survey among fresh leafy vegetable producers and wholesalers using structured questionnaire. A total of one hundred and eighty three (183) respondents were interviewed in order to obtain a survey on their attitude and factors that influenced the respondents’ attitude towards implementing post-harvest practices on fresh produce. A Likert scale of 1 to 5 (1 representing Strongly Disagree and 5 representing Strongly Agree) was used to measure respondents’ opinion and attitude on the statements related to the practice of postharvest. In this study, the descriptive analysis, factor analysis, and binary logistic regression were applied to analyze the gathered data. The findings indicate that both producers and wholesalers mainly have positive attitudes toward implementing post-harvest practices even though there were problems in implementing the practices. The respondents’ implementation of post harvest practices on fresh produce keeps on increasing due to consumers demand and requirement from the market. Based on factor analysis, four (4) factors were identified to influence producers’ attitudes toward implementing post-harvest practices. These factors are infrastructure, market availability, knowledge, and consumers’ concern. Meanwhile,from the wholesalers’ perspective, three (3) factors that influence wholesalers’ attitudes toward implementing post-harvest practices were identified and the factors are consumers’ concern, infrastructure, and market availability. The binary logit model was used to examine the attitudinal characteristics of fresh vegetable producers and wholesalers such as infrastructure, market availability, consumers’ concerns, knowledge, and socio-economic/demographic characteristics to determine the relative influence of socio-economic/demographic variables and other attributes on the attitudes toward the implementation of post-harvest handling practices. Research findings revealed that some of the parameters were significant in explaining the respondents’ attitudes toward implementing post-harvest practices. From the producers’ perspective, it was identified that there are three important determinants; infrastructure, market availability, and knowledge with significant predictors in explaining the producers’ attitude towards implementing post-harvest practices. Meanwhile for wholesalers, it was identified that three important determinants; consumers’ concerns, infrastructure, and availability of market are the significant predictors in explaining the wholesalers’ attitude towards implementing post-harvest practices. The concept of post-harvest practices is new in Malaysia but it becomes more popular among every player in the supply chain; from producers/growers to retailers as the society becomes more aware of the issues concerning to health and food safety. Besides that, it is important to improve the attitudes of every player in the supply chain in line with providing proper and sufficient infrastructure. Furthermore, quality plays an important role in ensuring the competitiveness and sustainability of vegetables industry in Malaysia. Besides reducing post-harvest losses, appropriate, and efficient post-harvest technology also helps to maintain the quality of vegetables for an extended period. Appropriate post-harvest practices willincrease added value to the fresh produce. Hence, the government, policy makers, related institutions, and food processers are responsible to educate and take action towards every player in the supply chain in implementing post-harvest practices.